Nanofocused scanning X-ray fluorescence microscopy revealing an effect of heterozygous hemoglobin S and C on biochemical activities in plasmodium falciparum-infected erythrocytes - Fröhlich, Benjamin; Yang, Yang; Thoma, Judith; Czajor, Julian; Lansche, Christine; Sanchez, Cecilia P.; Lanzer, Michael; Cloetens, Peter; Tanaka, Motomu (Analytical chemistry, 2020)
While there is ample evidence suggesting that carriers of heterozygous hemoglobin S and C are protected from life- threatening malaria, little is known about the underlying biochemical mechanisms at the single cell level. Using nanofocused scanning X-ray fluorescence microscopy, we quantify the spatial distribution of individual elements in subcellular compartments, including Fe, S, P, Zn, and Cu, in Plasmodium falciparum-infected (P. falciparum-infected) erythrocytes carrying the wild type or variant hemoglobins. Our data indicate that heterozygous hemoglobin S and C significantly modulate biochemical reactions in parasitized erythrocytes, such as aberrant hemozoin mineralization and a delay in hemoglobin degradation. The label-free scanning X-ray fluorescence imaging has great potential to quantify the spatial distribution of elements in subcellular compartments of P. falciparum-infected erythrocytes and unravel the biochemical mechanisms underpinning disease and protective traits.
Gesehen am 02.07.2020